Active Cool Roof System for The Attic Temperature Reduction - Wong, Song Wei (2019)
This research project investigates the cooling effect of an active cool roof system which is designed to enhance the comfortability of building occupants with attic temperature reduction. Malaysia is considered as an equatorial climate country which having a hot-humid climate all the year. Therefore, an ideal cool roof system was developed with the implementation of thermal insulating coating (TIC), MAC-solar powered fan, and rainwater harvesting system as a space cooling device for houses in Malaysia. Four small scale cool roof models were designed and fabricated to investigate the attic temperature cooling performance that executed by different cool roof configurations. The model simulation was carried out indoor by utilising the halogen lamp as the replacement for solar irradiation provided by the sun. The surrounding ambient temperature was controlled to be around 29.8 ℃ during the model testing. The temperature of the roof top surface, MAC aluminium tube, and the attic region was measured by K-type thermocouples in order to evaluate the cooling effect of the cool roof designs. Two active cooling methods were introduced in this research project which are the MAC-solar powered fan and rainwater harvesting system. All the solar fans were energized by the solar isolation that received by the solar panel which considered as a carbon neutrality energy. The solar powered fans were incorporated into the MAC which accelerated the airflow rate within the cavity and reject the hot air out before it transfer to the attic region. Meanwhile, the rainwater harvesting system was implemented to cool down the roof top temperature that reduce the rate of heat transfer from the roof top to the attic region. An automated actuate system (thermostat) was installed with the water pump to reduce the roof top temperature efficiently. In addition, a small scale cooling tower, solar panel, solar powered fan, and power filter were installed to enhance the cooling performance of the rainwater harvesting system. The result of this eco-friendly cool roof system (design Z) has successfully reduced the attic temperature by 4 ℃ compared to the normal TIC coated cool roof model (design W). As result, this integrated cool roof design comprises the ability to enhance the comfortability of building occupants with sustainable renewable energy.